2022
DOI: 10.3389/fpubh.2021.764198
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of Depression on the Relation Between Interpersonal Needs and Suicidal Ideation Among Chinese Transgender Women

Abstract: BackgroundTransgender women are at high risk of depression and suicidal ideation. The interpersonal theory of suicide proposes that suicidal ideation could be a consequence of high interpersonal needs (thwarted belongingness and perceived burdensomeness). The current study tests this theory and investigates whether depression could mediate the relationship between interpersonal needs and suicidal ideation among transgender women in Shenyang, China.MethodsA total of 198 transgender women were recruited by snowb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In addition, these two IPVs appear through physical and verbal IPV among TW, which lead to non-significant results. Although some studies showed that both IPV and CSEs are associated with depression ( 12 , 35 ), anxiety ( 50 , 51 ), post-traumatic stress disorder (PTSD) ( 35 , 52 ), etc., which are related to suicide ( 7 , 10 , 30 , 53 ), few studies explored whether these factors mediate the pathway from IPV/CSEs to suicidal ideation. Future research is needed to focus on the processes or mechanisms among these factors, especially among TW in China.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these two IPVs appear through physical and verbal IPV among TW, which lead to non-significant results. Although some studies showed that both IPV and CSEs are associated with depression ( 12 , 35 ), anxiety ( 50 , 51 ), post-traumatic stress disorder (PTSD) ( 35 , 52 ), etc., which are related to suicide ( 7 , 10 , 30 , 53 ), few studies explored whether these factors mediate the pathway from IPV/CSEs to suicidal ideation. Future research is needed to focus on the processes or mechanisms among these factors, especially among TW in China.…”
Section: Discussionmentioning
confidence: 99%